2015
DOI: 10.2147/copd.s82781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the COPD Assessment Test and GOLD patient types: a cross-sectional analysis

Abstract: BackgroundThe COPD Assessment Test (CAT) has been recently developed to quantify COPD impact in routine practice. However, no relationship with other measures in the Global Initiative for Obstructive Lung Disease (GOLD) strategy has been evaluated. The present study aimed to evaluate the relationship of the CAT with other GOLD multidimensional axes, patient types, and the number of comorbidities.MethodsThis was a cross-sectional analysis of the Clinical presentation, diagnosis, and course of chronic obstructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
13
2
Order By: Relevance
“…CAT has been developed to quantify COPD impact in routine clinical practice, and it has become one of the main tools in the recognition of health status in the disease. 28 In our study, CAT scores did not differ in COPD and ACOS patients; however, we did find an association between CAT scores and 25(OH)D level in ACOS group, but not in COPD patients. This observation supports the hypothesis that vitamin D level may have a stronger effect on health status in ACOS patients, than in COPD subjects.…”
Section: Discussioncontrasting
confidence: 75%
“…CAT has been developed to quantify COPD impact in routine clinical practice, and it has become one of the main tools in the recognition of health status in the disease. 28 In our study, CAT scores did not differ in COPD and ACOS patients; however, we did find an association between CAT scores and 25(OH)D level in ACOS group, but not in COPD patients. This observation supports the hypothesis that vitamin D level may have a stronger effect on health status in ACOS patients, than in COPD subjects.…”
Section: Discussioncontrasting
confidence: 75%
“…This is consistent with the findings from other studies showing that an mMRC grade of 2 generally equates to an average range of CAT score of 16 to 20. [26][27][28] In contrast, GOLD uses a CAT score of 10 or an mMRC score of 2 to establish a boundary between GOLD A/C (fewer symptoms) and GOLD B/D (more symptoms) patient subgroups. 1 Although GOLD does not state that the CAT and mMRC scores are related and recognizes that these patient-reported outcomes have different purposes, additional studies to generate data and a framework of reference are needed to confirm whether the CAT score of 10 is an appropriate cutoff point.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some patients with severe airflow obstruction did not complain of any symptoms [5]. Other studies demonstrated a wide distribution of the COPD assessment test, a score representing disease impact on patient's life, with respect to GOLD stage [6]. Even the time course of bronchial obstruction is variable, with a different FEV1 decline within GOLD stages [7].…”
Section: Introductionmentioning
confidence: 99%